The Effectiveness of Applying Mind Mapping Strategy on Student Speaking Ability - Ida Nuraida (Journal of English Language Teaching and Cultural Studies, 2018)
The Objective of the research are: 1) to know the effectiveness of applying Mind Mapping strategy on student speaking ability. 2) to determine the effectiveness of applying Mind Mapping Strategy to student’ speaking ability  3) to ascertain the effectiveness of applying Mind Mapping Strategy to student’ speaking ability. 4) to know the impact of applying Mind Mapping Strategy to student’ speaking ability. The population of the research was all of the six grades student and the sample was VI B with 40 student as an Experimental Class And VI A with 40 student as a control class. The methodology of the research was quasi-experimental design with the equivalent Control group design, in which the writer provided the pretest and posttest which are given to the experimental Class and Control class. The score was taken from the pretest and posttest which are given on the student belong to experimental class and control class. The average score of pretest of experimental class and are 66.625, and posttest score area 79.625, and also the pretest for control class are 64.750 and the posttest are 74.875. To prove the hypothesis, the writer counted the significance by using t test. Based on the distribution table t 5% significance and of 78, the t table is 0,02 0.05(0.050-0.05), so all the t count in the table is higher than t table. Therefore, Ho is rejected and Ha is received.